2014
DOI: 10.1177/0268355514554638
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal duplex ultrasonography appears to be the gold standard investigation for the haemodynamic evaluation of pelvic venous reflux in the ovarian and internal iliac veins in women

Abstract: Currently there is no accepted gold standard for pelvic vein incompetence. Comparing transvaginal duplex ultrasonography with the outcome from selectively treating the veins identified as having pathological reflux with coil embolisation, there were no false-negative diagnoses and only one false-positive. This study suggests that transvaginal duplex ultrasonography could be the gold standard in assessing pelvic vein reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 20 publications
2
54
0
2
Order By: Relevance
“…However, in a case report by Oğuzkurt et al [3] , a diagnosis of MTS was initially reached by transabdominal ultrasonography alone and later confirmed by CT, venography, and pressure measurements. Although transvaginal ultrasound can be used to determine the pathological reflux in the internal iliac veins in women, it does not allow for good imaging of the common iliac veins and is therefore not a very useful tool in the diagnosis of MTS [19] . Overall, ultrasound is a useful mechanism for determining venous patency, but a negative study result does not rule out the possibility of MTS and therefore more imaging tests are needed in order to establish a diagnosis.…”
Section: Mrvmentioning
confidence: 99%
“…However, in a case report by Oğuzkurt et al [3] , a diagnosis of MTS was initially reached by transabdominal ultrasonography alone and later confirmed by CT, venography, and pressure measurements. Although transvaginal ultrasound can be used to determine the pathological reflux in the internal iliac veins in women, it does not allow for good imaging of the common iliac veins and is therefore not a very useful tool in the diagnosis of MTS [19] . Overall, ultrasound is a useful mechanism for determining venous patency, but a negative study result does not rule out the possibility of MTS and therefore more imaging tests are needed in order to establish a diagnosis.…”
Section: Mrvmentioning
confidence: 99%
“…While the authors cannot verify the "true" initial state of the overtreated veins, those that have been undertreated were shown to have persistent reflux at a follow-up TVS almost 100% of the time. 23 Fig . 2 shows the distribution of vessel diameters for both groups.…”
Section: Classmentioning
confidence: 99%
“…Since the first description of the link between pelvic varicosities and pelvic symptoms was made by Taylor in 1949 1 , the diagnosis of pelvic congestion syndrome has relied upon the combination of one or more clinical symptoms in conjunction with the presence of pelvic varicosities, proven reflux or obstruction in the pelvic veins and a recent Heath Technology Assessment stated that "Pelvic congestion syndrome (PCS) is described as chronic pelvic pain (CPP) arising from dilated and refluxing pelvic veins … " 2 . Fortunately, in our experience, obstructive disease is rare in PCS 3 and usually presents with different signs or symptoms such as visible supra-pubic or flank varicosities in May-Thurner type obstructions, or left flank pain in nut-cracker syndrome.…”
Section: Introductionmentioning
confidence: 75%
“…It is easy to scan patients in a 45 head-up position, allowing gravitational reflux to be observed. However, although the truncal ovarian veins can be assessed in slim subjects transabdominally, research published from our unit has shown that the vast majority of patients (97%) with PVR have reflux in at least one internal iliac vein territory 3 . As this reflux is often in the pudendal or obturator veins, it is usually impossible to see this reflux using TADUS.…”
Section: Optimal Diagnostic Test For Pelvic Venous Reflux and Objectimentioning
confidence: 99%